Staple food circuits in the Ouagadougou – Accra corridor : conditions of an inclusive development - (:unkn) unknown (My University, 2017)
Since colonization, West African transport corridors drew an economic dependence on space towards gobalized market. Massive imports of manufactured goods are not yet balanced by the export of raw materials. The African market is not yet a market for Africans and this generally hampers territorial development. In the transport corridor between Ouagadougou and Accra, in West Africa, the challenges of regional integration and food security are crystallizing in the staple food circuits. The exchanges taking place there regulate the mobility of foodstuffs between places. In the space constituted by Burkina Faso and Ghana, characterized by an ecological gradient between the Sahel and the coast that strongly differentiates agricultural potentialities, the thesis puts these challenges in perspective with territorial development. We analyze the inclusive potential of merchant staple food circuits through the example of yam, maize and cowpea in the corridor that connects Ouagadougou to Accra. After analyzing the transactional practices of these circuits based on surveys carried out with traders and transporters in the field, we simulate potential exchanges using a gravity model. We use for this data relating to production, trade and consumption and we assess spatial accessibility through localized road data. Between food availability and household demand, locating these exchanges and their paths questions the articulation of the food trade scales and the complementarity of places and activities regarding the links between agriculture, trade and transport identified as carriers of spatially inclusive development. In a context of secondary cities, margins and borders, our approach explores the spatial interactions between surplus and deficit areas. Our main goal is to propose technical recommendations with operational and political scope to contribute to the debate on regional integration and food security.
Keywords: African Research